Cross-Border Economy in LMC Region: Poverty Alleviation and Common Prosperity* - Renliang, Li; Chouykerd, Prateep; Yu, Cheng; Tingting, Guo; Sriruang, Jirawat (Journal of Social Development and Management Strategy, 2024)
This research aims to 1) study the existing cross-border trade, channels of trade, means of payment, mode of transportation and related regulations in LMC region, focusing on Thailand, Laos and China; 2) explore the possibilities and challenges in transforming and upgrading a cross-border economy by applying China’s wisdom and model of targeted poverty alleviation in the region; 3) make policy recommendations to upgrade cross-border economy towards poverty alleviation and common prosperity in LMC region. A qualitative approach is adopted to achieve the research objectives. The research methods employed include documentary research, in-depth interviews, and case studies. The research findings suggest that 1) cross-border trade in the LMC region is primarily conducted through established trade routes and border checkpoints. These trade routes are crucial for facilitating the movement of goods and services between the three countries. The channels of trade identified include land, air, and water transportation. Land transportation, particularly road networks, is the most commonly used mode for cross-border trade in the LMC region. Means of payment in cross-border trade vary, with cash, bank transfers, and digital payment systems being the most prevalent; 2) applying China’s wisdom and model of targeted poverty alleviation in the LMC region holds significant potential for transforming and upgrading the cross-border economy. China’s experience in poverty alleviation through targeted interventions, infrastructure development, and capacity-building programs can be adapted and utilized to address poverty challenges in the LMC region; 3) the following policy recommendations are proposed: promoting regional integration is crucial for economic growth and development; facilitating trade is essential for economic growth and poverty reduction; creating a conducive environment for investment is necessary to foster economic development; promoting entrepreneurship is vital for economic growth and job creation; strengthening regional cooperation is crucial for economic development.